Cytological Aspects of Equine Oral Fibrosarcoma - Martins, Danieli Brolo; Rossato, Cristina Krauspenhar; Abrão, Nadjanaira Barbosa; da Luz, Mariela (Acta Scientiae Veterinariae, 2019)
Background: Although mesenchymal neoplasms are prominent in horses due to the occurrence of sarcoids, other neoplasms may occur. Fibrosarcoma in horses is uncommon, notwithstanding, few studies have performed diagnostic techniques. It is presumed, therefore, that other diagnostic methodologies should be explored. In this sense, fine needle aspiration cytology (FNAC) emerges as an effective, low-cost, and minimally invasive method to identify tumors in these animals. The objective of this study was to describe the use of FNAC in the diagnosis of oral fibrosarcoma in horses. Once fibrosarcoma is an aggressive tumor, it is important to validate effective techniques for an early diagnosis. Case: A 10-year-old male Quarter Horse was treated, with a clinical complaint of increased volume in the right maxillary region. This tumor occupied about ¼ of the hard palate area. Hyporexia, hypodipsia, mild dehydration, and weight loss were observed at clinical examination. Complementary examinations were requested, and an extensive radiolucent mass with an indication of bone involvement was observed on the radiograph. The hemogram revealed normocytic normochromic anemia, in addition to lymphopenia. In the serum biochemistry test, AST (aspartate aminotransferase) and creatinine were slightly increased. FNAC showed a malignant mesenchymal neoplasm, possibly fibrosarcoma. Due to its clinical worsening and lack of response to supportive treatment, humanitarian euthanasia was performed. Finally, a histopathological examination confirmed the oral fibrosarcoma suggested by FNAC. Discussion: The early diagnosis of neoplasms is important for its correct treatment, as well as the prognosis. In this way, the combined use of complementary tests helps in the resolution of the case. FNAC is still little used in the examination routine in horses. In the present report, this test demonstrated efficacy since it revealed mesenchymal cells compatible with fibroblasts, in addition to malignancy characteristics such as cells with anisocytosis, cytoplasmic basophilia, macrocariosis in some cells, round to elongate nuclei, coarse chromatin, prominent nucleoli, and a discrete eosinophilic amorphous matrix between the cells. The other laboratory findings were consistent with the disease. Normocytic normochromic anemia is found in chronic conditions, such as neoplasms, and lymphopenia may be a finding in stress situations. The anatomical location of the tumor and the bone involvement made surgical treatment impossible. With this, we sought to alleviate the patient's discomfort with supportive therapy, which in situations of chronicity is not always effective, as in the case described. In conclusion, FNAC can be used to differentiate malignant tumors from those considered benign, as well as in the identification of tumor groups. Despite the high predictive value of FNAC, histopathological examination was fundamental for the categorization of the neoplasia. Therefore, it is recommended to confirm the FNAC result by histopathology since equine fibrosarcoma can be easily confused with other malignancies more common in the species, such as sarcoids. The cytological examination showed a correct orientation in this case. Nonetheless, further studies are needed to demonstrate the applicability of this technique in increased oral volume in horses.